Relationship of viral infections and multiple sclerosis. Modern trends in the diagnosis and treatment of multiple sclerosis - Davydova, T; Volyanskiy, A; Martynov, A (Annals of Mechnikov's Institute, 2019)
Multiple sclerosis (MS) is a polyethiological disease that develops as an interaction between the immune system and external factors in genetically susceptible individuals. There is growing evidence that viruses can play a role in the pathogenesis of MS, acting as external triggers. However, it is not fully known whether a single virus is causal or several viruses can act as an impulse to the development of the disease. We examined the association of various viruses with MS, focusing on two herpesviruses: human herpesvirus 6 (HHV-6) and Epstein-Barr virus (EBV). In recent years, the researchers have indicated that these two agents had the greatest impact as possible co-factors in the development of the disease. The most important evidence in favor HHV-6 and EBV association is the link between symptoms infectious mononucleosis and the persistent chronic process caused by EBV and HHV-6 with MS, serological data and viral load detection in MS patients. But it is know that the mononucleosis symptoms can be caused by other members of the herpes group. HHV-6 is significantly more likely detected in MS plaques, in contrast to EBV, in comparison with the results studies brain tissue and non-MS patients. And it was observed HHV-6 activation during MS relapses. Herpes viral load peripheral blood mononuclear cells (PBMCs), primarily EBV and HHV-6, was significantly higher in patients with MS than in the control group and was combined with changes in some parameters cellular and humoral immunity, significantly increasing in relapse periods of the disease. In this review, we propose new strategies, including the development of promising directions virological and immunological protocols MS diagnosis and treatment and formation clinical trials tactics, to find out the roles of different viruses and autoimmune processes in the MS pathogenesis to find a recovery algorithm for improving the life quality and possible MS problem solution. For the large-scale clinical studies that could confirm or refute viruses participation in the MS pathogenesis, especially herpes, the advisability of antiviral and immunotherapy, we offer the method of direct immunofluorescence, which has a number of advantages: speed processing; the ability to investigate the viral load in the affected cells in the body fluids and tissues; highly specific; informative and economically sound. Conclusions. This review discussed the role of infectious agents, mostly viruses, in the MS development and pathogenesis. Despite the presence links between MS and several viruses, it has not been proven that the virus is the cause of this neurological disease. Recently strong evidence focuses on the herpesvirus family member, such as EBV and HHV-6. Because these viruses are widespread among humankind, it creates unique challenges in establishing causation with MS. The isolation of the predicted agent from MS affected tissue, such as active plaques in the CNS; viral load PBMCs; and increasing the humoral and cellular immune response to these viruses in peripheral blood and liquor are strong arguments in support these viruses as triggers in the disease process. After all, only due to well-controlled trials of antiviral treatment causative or other pathogenetic link between these viruses and MS can be established.